Experimental study on frequency and amplitude characteristics of acoustic emission during the fracturing process of coal under the action of water. (August 2019) - Shen, Rongxi; Qiu, Liming; Zhao, Enlai; Han, Xu; Li, Hongru; Hou, Zhenhai; Zhang, Xuan
Highlights: Macro influence and micro mechanism for the action of water pressure on coal body. Variation characteristics of AE frequency during fracturing process of coal under the action of water pressure. Distribution law of AE amplitude during fracturing process of loaded coal under the action of water. Abstract: Under the action of water pressure, a large number of acoustic emission (AE) signals can be generated during the fracture process of coal samples under loaded, which contain abundant precursory information of coal failure. By coal compression experiments under the action of different pressure water, the law of amplitude-frequency characteristics and frequency band of AE signals has been analyzed in depth. The results show that: (1) By destructing the microstructure of coal, the physical and mechanical properties of coal is changed by water, resulting in the reduction of the ability to accumulate and release elastic energy. The greater the water pressure, the more difficult it is for coal samples to generate large-scale fractures, and that the frequency and amplitude characteristics of AE signals also change. (2) High-pressure water reduces the mechanical strength and brittleness of coal. The higher the water pressure, the more significant the effect. (3) The dominant frequency point of AE signals produced by the failure of coal under the action of water pressure usually lies between 50 kHz and 110 kHz. With the increase of the stress, AE signals show increasing low-frequency energy and decreasing high-frequency energy. (4) Due to the action of water, in the coal fracturing process of coal sample, the frequency of AE has changed. The proportion of low-frequency signals has decreased, while the proportion of high-frequency signals has increased. The greater the water pressure, the higher the dominant frequency point. (5) The amplitude of AE signals from coal sample fractures distributes between 40 dB and 80 dB. The higher the water pressure, the lower the maximum amplitude of AE signal. The study helps to better understand the effect of water pressure on the deformation and failure process of coal and rock, which is of great significance for avoiding coal and rock dynamic disasters related to water and ensuring mine safety in production.